Marine Fouling Panel Survey and Assessment of Marine Alien Invasive Species in Myanmar - Myint Myint Khaing (Universitas Gadjah Mada, 2018)
A survey on fouling using PVC panels was carried out for a period of one year in Yangon River. Additional observations on fouling of man-made structures elsewhere in Myanmar were also made in an effort to find marine alien invasive species. The Myanmar ports at Yangon, Sittway and Myeik have a long history of overseas trading with Europe since the 17th century. In addition, though the Yangon port and jetties are located upstream some 12 miles from the mouth of Yangon River, it experiences regular tidal action with seasonal brackish water conditions. Its catchment area is only 100 miles from the mouth and hence the river and its tributaries are short and small. Moreover, there are several weirs and small dams on the tributaries, which result in reduced sediment influx at the mouth and thus less turbidity. Therefore, the physiochemical conditions at Yangon port may not pose a limitation on the distribution of nuisance species that are able to survive brackish water conditions. Elsewhere, Sittway port at the mouth of the Kispanadi River also experiences regular tidal action and is directly connected to the Bay of Bengal, conditions which are favourable for the intrusion of marine nuisance species. Myeik port is located along the open shore of the Myeik, which is located near the Myeik Archipelago. The waters around the archipelago are clear and the shelf is characterized by high biodiversity. Therefore, the environment also appears to be highly favourable for alien invasive species. However, these ports have no record of the occurrence of alien invasive species in particular the Caribbean bivalve Mytilopsis sallei.